Determination of Airline Employee Performance: Analysis of Competence, Motivation, Mentoring, and Job Satisfaction (Library Research Model) - Agus Suhendra (Greenation Research & Yayasan Global Resarch National, 2026)
This study aims to analyze the determinants of employee performance in the aviation industry by examining the role of competence, motivation, mentoring, and job satisfaction. This study adopted a qualitative approach using a literature review method, synthesizing findings from previous studies published between 2021 and 2026 in reputable international and national journals. Data were collected from academic databases, including journals indexed by Elsevier, Emerald, Sage, Web of Science, Springer, EBSCO, Copernicus, and SINTA. Article selection was based on relevance, methodological rigor, and alignment with the research variables. Data were analyzed using thematic analysis to identify patterns, relationships, and conceptual insights across studies. This approach allows for a comprehensive understanding of how human resource factors influence employee performance in the aviation context. This study contributes to the development of a multidimensional framework that integrates key determinants of employee performance and provides strategic insights for improving human resource management practices in the aviation industry. The results of the study indicate that: 1) Competence influences Airline Employee Performance; 2) Motivation influences Airline Employee Performance; 3) Mentoring influences the performance of airline employees; 4) Job satisfaction influences the performance of airline employees.